Diseño de una secuencia didáctica para la enseñanza de la comprensión lectora inferencial en libro álbum con estudiantes de grados iniciales en la institución educativa Sagrado Corazón (2020)
This research project designed a didactic sequence aimed at teaching inferential reading comprehension in an album for first and second grade primary school students, Ricardo Cifuentes Riomaña, of the Sacred Heart of Cerrito Educational Institution, Valle from Cauca The purpose was to support the development of inferential thinking in children. The methodological design was framed within a qualitative approach, based on a type of descriptive and analytical research. Five thematic units were developed, making use of the album as a didactic tool. The narrative design was applied as a technique and instrument, which allowed the collection, treatment and analysis of the stories in the light of the theoretical objectives and constructs. It tries to motivate the student towards reading, since at the moment it is monotonous. Therefore, this work allows students to understand stories through images, optimizing their curiosity while working as a team.